An advanced dislocation density-based approach to model the tensile flow behaviour of a 64.7Ni–31.96Cu alloy - Joseph A.S.; Gupta P.; Kumar N.; Poletti M.C.; Yadav S.D. (My University, 2025)
Modelling the flow behaviour enables to understand the underlying deformation mechanisms underneath the various conditions imposed during the thermo-mechanical processing. Thus, herein flow stress response of 64.7Ni–31.96Cu alloy with different grain size is modelled at varying temperatures and strain rates, employing a dislocation density reliant physical model. The model takes account of immobile dislocations and assimilates strain hardening effect, Hall–Petch effect and the short-range interactions. Furthermore, the model addresses the static and dynamic recovery as key aspects during plastic deformation. In this advanced approach, the influence of twin boundaries has been incorporated and modelled flow curves show reasonable agreement with the experimental ones. The effect of different grain sizes and connected changes in the amount of twins on the flow stress can be obtained from the model. Predicted final dislocation densities and cell size are in the range of 6.91–10.26 × 1014 m−2 and 0.59–0.80 μm, respectively, for varying test conditions. It was observed that there is a sharp increase in dislocation density at the commencement of deformation. Concomitantly, hardening is also more profound during initial deformation. The investigation also revealed that excluding the twin boundaries in this physical-based approach would lead to underestimation of flow stress. This model also makes it possible to evaluate the relative contributions from different strengthening mechanisms. © 2022 Informa UK Limited, trading as Taylor & Francis Group.